1998
DOI: 10.1038/sj.jhh.1000479
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the arm position on intra-arterial blood pressure measurement

Abstract: The reference level for the measurement of blood pressure (BP) is the level of the right atrium. In practice this is regularly disregarded, as the patient's arm is usually placed lower than the right atrial level. The aim of the study was to determine the influence of first, different arm positions and second, different transducer positions on the intra-arterially (i.a.) recorded BP. In 16 healthy men (age 28.1 ± 8.0 (s.d.) years), i.a. BP was recorded at the left arm in supine position, using a 5-7 cm long ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 13 publications
4
27
0
Order By: Relevance
“…Our findings are supported by our earlier results with respect to the influence of arm position on intra-arterial BP readings 20 and by the results obtained in a previous epidemiological study 11 in a large group of healthy volunteers. The hydrostatic factors were considered the most important for the differences observed between the BP readings at different arm levels.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are supported by our earlier results with respect to the influence of arm position on intra-arterial BP readings 20 and by the results obtained in a previous epidemiological study 11 in a large group of healthy volunteers. The hydrostatic factors were considered the most important for the differences observed between the BP readings at different arm levels.…”
Section: Discussionsupporting
confidence: 91%
“…It is believed that the difference in BP values produced by arm movement is largely accounted for by hydrostatic pressure 5 and this is supported by Netea et al, 11 although the differences demonstrated in regression analysis between SBP and DBP in our study cast doubt on such a simplistic view.…”
Section: Discussionsupporting
confidence: 69%
“…These important observations have been replicated using an oscillometric device 10 and confirmed by intraarterial BP measurements. 11 Despite studies confirming the importance of arm position on BP measurement, it is likely that arm position varies markedly in clinical practice and also in published studies. Resting an arm on a desk or arm of a chair as often recommended could vary the BP significantly, depending not just on the dimensions of the furniture but also on the height of the individual and also their posture.…”
Section: Introductionmentioning
confidence: 99%
“…A possible explanation for the difference between these two studies could be the fact that oscillometric instruments were used in the present study, whereas standard mercury sphygmomanometers were used in the study of Ljungvall et al 4 However, the differences we obtained are closer to those theoretically expected, when one considers the effects of hydrostatic forces as a major determinant of the differences in BP between the two positions. 17 Differences of 3-4 mmHg may be small as absolute value, but are still important in epidemiological terms.…”
Section: Discussionmentioning
confidence: 99%